Projected Effects of Climate-Induced Changes in Hydrodynamics on the Biogeochemistry of the Mediterranean Sea Under the RCP 8.5 Regional Climate Scenario - Pagès, Rémi; Baklouti, Melika; Barrier, Nicolas; Ayache, Mohamed; Sevault, Florence; Somot, Samuel; Moutin, Thierry (Frontiers in Marine Science, 2020)
The Mediterranean region has been shown to be particularly exposed to climate change, with observed trends that are more pronounced than the global tendency. In forecast studies based on a RCP 8.5 scenario, there seems to be a consensus that, along with an increase in temperature and salinity over the next century, a reduction in the intensity of deep-water formation and a shallowing of the mixed layer (especially in the North-Western Mediterranean Sea (MS)) are expected. By contrast, only a few studies have investigated the effects of climate change on the biogeochemistry of the MS using a 3D physical/biogeochemical model. In this study, our aim was to explore the impact of the variations in hydrodynamic forcing induced by climate change on the biogeochemistry of the MS over the next century. For this purpose, high-resolution simulations under the RCP 8.5 emission scenario have been run using the regional climate system model CNRM-RCSM4 including the NEMO-MED8 marine component, coupled (off-line) with the biogeochemical model Eco3M-Med. The results of this scenario first highlight that most of the changes in the biogeochemistry of the MS will occur (under the RCP 8.5 scenario) after 2050. They suggest that the MS will become increasingly oligotrophic, and therefore less and less productive (14 % decrease in integrated primary production in the Western Basin and in the Eastern Basin). Significant changes would also occur in the planktonic food web, with a reduction (22 % in the Western Basin and 38 % in the Eastern Basin) of large phytoplankton species abundance in favour of small organisms. Organisms will also be more and more N-limited in the future since NO3 concentrations are expected to decline more than those of PO4 in the surface layer. All these changes would mainly concern the Western Basin, while the Eastern Basin would be less impacted.